Optimal resource allocation for hybrid interweave-underlay cognitive SatCom uplink - Zuo, PeiLiang; Peng, Tao; Linghu, Wangdan; Wang, Wenbo (2018 IEEE Wireless Communications and Networking Conference (WCNC), 2018)
Cognitive satellite terrestrial networks have received widespread attention recently for improving the spectrum utilization. In this paper, a hybrid interweave-underlay spectrum access (HIUSA) scheme based on spectrum sensing in 5GHz license-exempt spectrum is proposed, which eliminates the performance degradation brought by inaccurate parameters estimation of the interference link in a large extent, and enhances the throughput of the cognitive system substantially. While analyzing relevant details, we also focus on the resource allocation (RA) problem in this scenario, the RA problem takes the maximum throughput of the cognitive satellite communications (SatCom) as target, and subjects to the requirements of cognitive terminals. Then, the convex RA problem is solved by a simplified iteration algorithm. Extensive simulation results are given to demonstrate the performance and effectiveness of the proposed HIUSA scheme as well as the RA approach, by contrasting with the legacy system as well as the common method.